2010
DOI: 10.1016/j.cgh.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-Producing Neoplasms of the Pancreas: An Analysis of Distinguishing Clinical and Epidemiologic Characteristics

Abstract: BACKGROUND & AIMS Mucin-producing neoplasms (MPNs) of the pancreas include mucinous cystic neoplasms (MCNs) and main-duct, branch-duct, and combined intraductal papillary mucinous neoplasms (IPMNs). MCNs and branch-duct IPMNs are frequently confused; it is unclear whether main-duct, combined, and branch-duct IPMNs are a different spectrum of the same disease. We evaluated their clinical and epidemiologic characteristics. METHODS Patients who underwent resection for histologically confirmed MPNs were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
2
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(236 citation statements)
references
References 24 publications
5
217
2
12
Order By: Relevance
“…MCNs occur almost exclusively in female, such as male cases are reported to be extremely rare [9][10]. The median age of presentation is reported to be 48 (range 16-82) and tumors are preferentially located in the body/tail of the pancreas [11,12]. Patients with malignant MCNs are typically older, suggesting a time-related degeneration of the tumor from an initially benign lesion.…”
Section: Mucinous Cystic Neoplasmmentioning
confidence: 99%
See 2 more Smart Citations
“…MCNs occur almost exclusively in female, such as male cases are reported to be extremely rare [9][10]. The median age of presentation is reported to be 48 (range 16-82) and tumors are preferentially located in the body/tail of the pancreas [11,12]. Patients with malignant MCNs are typically older, suggesting a time-related degeneration of the tumor from an initially benign lesion.…”
Section: Mucinous Cystic Neoplasmmentioning
confidence: 99%
“…We are nowadays aware that IPMNs are the most frequently detected pancreatic cysts, representing 39 % of the cystic surgical series [8]. Patients undergoing resection are typically in their sixth decade of life [11] with a slightly higher incidence for males. IPMNs can be either sporadic or associated with familial syndromes such as Peutz-Jeghers syndrome (PJS) and familial adenomatous polyposis (FAP).…”
Section: Intraductal Papillary Mucinous Neoplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, survival outcomes are still favorable despite the second resection. Also, even though these intraductal neoplasms may develop invasive carcinoma, usually in the form of invasive oncocytic or mucinous (colloid-like) carcinoma, they still have more indolent course than conventional PDAC (16,31,38,40,71,121,124,126,133).…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…We have shown that main-duct and mixed-type IPMNs are more likely to have invasive carcinoma compared with branchduct type (48% and 42% vs 11%) and, subsequently, 5-year disease specific survival rates of main-duct and mixed-type IPMNs are significantly lower than that of branch-duct type (65% and 77% vs 91%). 5 Histologically, IPMN is thought to progress from low-grade dysplasia (adenoma) to intermediate-and high-grade dysplasia (carcinoma in situ) and invasive carcinoma. 36 While the 5-year survival of patients with resected non-invasive IPMN is as high as 77%-94%, invasive IPMN carries a poorer survival of 33%-43%.…”
Section: Introductionmentioning
confidence: 99%